Educational design of live coding environments for the browser. Issue 1 (1st May 2016) - Roberts, Charlie; Allison, Jesse; Holmes, Daniel; Taylor, Benjamin; Wright, Matthew; Kuchera-Morin, JoAnn
Gibber is a creative coding environment for the browser designed for live coding performance and education. It emphasizes a simple notation, a strong audio-visual feature set, immediate feedback, and social collaboration. We describe the use of Gibber and its supporting libraries in a variety of educational settings, from work with a summer camp for middle-school girls to university electroacoustic ensembles. We also describe early results designing a new environment, called Braid, for live coding browser-based digital musical instruments (DMIs) that is informed by our teaching experiences.